An electronic readiness assessment model for electronic commerce adoption by Iranian small and medium contractors - Kianosh Naserolmemar, 1973-, author; Rosli Abdul Rashid, supervisor; Fakulti Alam Bina (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Ukur Bahan)) - Universiti Teknologi Malaysia, 2016